Genotoxicity of fumonisin B1, beauvericin and ochratoxin A in porcine kidney PK15 cells : effects of individual and combined treatment - Šegvić Klarić, Maja (Array, 2008)
Summary: After 24- and 48-hour treatment with 0.05, 0.5 and 5 mg/mL of fumonisin (FB1), beauvericin (BEA) and ochratoxin A (OTA) alone or combinations of two or all three mycotoxins in equal concentrations, Giemsa-stained binucleated PK15 cells were scored for the presence of micronuclei (MN), nuclear buds (NBs) and nucleoplasmic bridges (NPBs). Single mycotoxins induced MN and NPBs in a dose-dependent manner, showing predominantly clastogenic effect. OTA showed stronger genotoxic potential than FB1 and BEA, since 0.05 and 0.5 mg/mL OTA increased the frequency of MN and NPBs, respectively. Mycotoxin combinations increased the frequency of MN and NPBs, mostly in additive manner. A dose-dependent increase in NBs was observed after 24-hour exposure to single mycotoxins. Prolonged treatment with 5 mg/mL of each toxin alone as well as combined exposure to all mycotoxin concentrations resulted in a decrease in NBs, which could be related to the extrusion of micronuclei and/or saturation of the genotoxic effect. This is the first report on genotoxicity of BEA